Do farmers' socio-economic characteristics influence their preference for agricultural extension methods?. Issue 7 (3rd October 2019) - Mwololo, Henry; Nzuma, Jonathan; Ritho, Cecilia
ABSTRACT: This article assesses the influence of farmer socio-economic factors on their preferences for agricultural extension methods. Cross-sectional data of 816 households were collected using multistage sampling procedure. Descriptive results show that the training and visit, farmer field schools, mass media and farmer-to-farmer extension methods were preferred by 42%, 32%, 13%, and 13% of the farmers, respectively. Regression estimates show that education, access to markets, risk attitudes and wealth significantly influenced farmers' preferences for extension methods. The article concludes that farmers' socio-economic characteristics should be considered in the selection and use of agricultural extension methods.